Microbiological mechanisms of oral mucosal disease: oral-intestinal crosstalk and probiotic therapy - Zhou, Qi; Liu, Panpan; Chen, Muni; He, Hao; Xu, Mengting; Xu, Qianrong; Yu, Jianfeng; Deng, Yutian; Yan, Jiayu; Wen, Yueqiang (Frontiers in Oral Health, 2025)
Balance of the oral-intestinal axis microbiota is essential for maintaining oral mucosal health. The occurrence of oral disease is closely linked to the microbiota, this disorder is closely related to the pathogenesis of oral mucosal diseases, such as oral lichen planus, recurrent aphthous ulcer, oral candidiasis and squamous-cell carcinoma. As a microorganism that is beneficial to host health, probiotics can show multi-dimensional therapeutic effects in oral mucosal diseases by targeting and regulating the immune microenvironment of the oral mucosa, inhibiting the colonization of pathogenic bacteria and repairing the barrier function. In this review, we will review the relevant roles that oral-gut microbial homeostasis plays in the pathogenesis of oral mucosal diseases and provide evidence for dysregulation of microbial homeostasis in patients with oral mucosal diseases, and explore specific probiotic strains by regulating oral and intestinal axis microbial homeostasis and host immune and inflammatory responses, in order to provide new ideas for the clinical treatment of oral mucosal diseases.